Perspectives for the implementation of a closed-cycle economy in Russia ("Journal "U". Economy. Management. Finance.", 2024)
In today's world, the problem of rational use of resources and preserving the ability of the environment to maintain a sustainable ecosystem is increasing. At the same time, the amount of waste produced by businesses is increasing, leading to environmental degradation and resource scarcity. The concept of the circular economy is an alternative approach to doing business that can significantly reduce waste, increase resource efficiency and reduce environmental impact.
Keywords: circular economy; sustainable development; waste recycling; ecology; innovation; energy efficiency; renewable energy sources; circular model; linear economy; environmental literacy